Differences of alt-ast level and snail gene expression between patients with metastasis and non-metastasis colorectal cancer - Chrisna Budi Satriyo; Hendra Susanto; Adeodatus Yuda Handaya; Nurcahya Setiawan; Imam Sofii; Agus Barmawi (Faculty of Medicine, Universitas Islam Indonesia, 2022)
Background: Colorectal cancer (CRC) is a malignant epithelial tumour in the colon and rectum, and its main cause is distant metastasis. The main process of distant metastasis is the epithelial-mesenchymal transition (EMT) that may cause mesenchymal phenotype and malignant capabilities of tumour cells. Then it is regulated by one of transcription factors, the Snail.Objective: This study aims to determine differences between Snail gene expression in CRC that has not metastasized and Snail gene expression in CRC that has metastasized. Methods: The subjects of this study consisted of two groups of patients. The first group consisted of 20 patients with CRC (tumour), and the second group consisted of 12 patients with CRC with metastasis (metastasis tumour). The Snail gene expression was measured in both groups by using the RT-qPCR method and supported by laboratory examination to measure ALT and AST. Then all obtained data were analysed by using a statistical software analysis.Results: This study indicated that there were differences of the Snail gene expression between both the groups, and the highest expression was in the metastatic tumour group with a significance level of 0.002 (p<0.05). This was also supported by AST and ALT which were significantly correlated between both the groups. The correlation value on the AST was 0.506 with a significance level of 0.003, and the ALT correlation value was 0.532 with a significance level of 0.002. Conclusion: This study suggested that the Snail was a potential marker of metastasis in the CRC. Therefore, further research is needed to determine the role of Snail regulation in the CRC metastasis.